Implementasi Tata Tertib Sekolah Dengan Pemberian Hadiah Dan Hukuman Dalam Pembentukan Kedisiplinan Siswa (Studi Di SDN 2 Rancabango Kecamatan Tarogong Kaler-Kabupaten Garut) - Sulaiman, Husnan; Aripin, Ipin (MASAGI : Jurnal Pendidikan Agama Islam, 2022)
The presence of rule violations at SDN 2 Rancabango prompted this research. Additionally, the inconsistent enforcement of school regulations has led to numerous infractions by students. This study aims to understand the implementation of school rules through the use of rewards and punishments in fostering student discipline at SDN 2 Rancabango, Tarogong Kaler District, Garut Regency. The research method used is field research with a qualitative descriptive approach, which involves working with data by recording, collecting, organizing, searching for patterns, identifying important aspects, and analyzing them in written form. Based on observations, interviews, and documentation, it can be concluded that the implementation of school rules, along with the use of rewards and punishments, impacts student discipline at SDN 2 Rancabango. Effective reward systems can motivate students to adhere to school regulations. Every student appreciates rewards, making them a powerful method to ensure compliance with school rules. However, rules will not be followed without the presence of strict punishments. Keywords: Implementation of School Rules, Rewards, Punishments, Discipline